Two-dimensional hexagonal SnS2 nanostructures for photocatalytic hydrogen generation and dye degradation. Issue 12 (30th September 2019) - Damkale, Shubhangi R.; Arbuj, Sudhir S.; Umarji, Govind G.; Panmand, Rajendra P.; Khore, Supriya K.; Sonawane, Ravindra S.; Rane, Sunit B.; Kale, Bharat B.
Abstract : Two-dimensional (2D) hexagonal tin disulfide (SnS2 ) nanostructures were prepared via a hydrothermal method using ethylenediamine as a capping agent. Abstract : Two-dimensional (2D) hexagonal tin disulfide (SnS2 ) nanostructures were prepared via a hydrothermal method using ethylenediamine as a capping agent. The structural study indicates the formation of the hexagonal phase of SnS2 for all the samples synthesized under different conditions. The band gap of samples was observed to be in the range of 2.32 to 2.40 eV. A morphological study by FESEM and FETEM of SnS2 prepared at 200 °C for 24 h shows the formation of highly crystalline hexagonal nanoplates of 200–600 nm diameter with 20–30 nm thickness. Furthermore, the selected area electron diffraction pattern and high resolution TEM image validate the hexagonal phase of SnS2 . Different experimental parameters were investigated to examine the phase and morphology. The formation and growth mechanism has also been proposed based on the experimental conditions and parameters. The photocatalytic performance of SnS2 nanoplates was examined for H2 generation via water splitting under a 400 W mercury vapor lamp. The highest H2 evolution (522.4 μmol per 0.1 g i.e. 1306 μmol h −1 g −1 ) was observed for SnS2 nanoplates synthesized for a longer time and at a higher temperature i.e. 24 h and 200 °C. The same sample also shows 85% photocatalytic methylene blue (MB) dye degradation within two hours with a rate constant value of around 17.8 × 10 −3 ± 4.3 × 10 −3 min −1 . This study provides a simple and inexpensive way to prepare highly active SnS2 nanoplates.